2019
DOI: 10.1038/s41598-019-45621-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally varying effects of environmental factors on phytoplankton abundance in the regulated rivers

Abstract: This study investigates a seasonally varying response of phytoplankton biomass to environmental factors in rivers. Artificial neural network (ANN) models incorporated with a clustering technique, the clustered ANN models, were employed to analyze the relationship between chlorophyll a ( Chl-a ) and the explanatory variables in the regulated Nakdong River, South Korea. The results show that weir discharge ( Q ) and total phosphorus ( TP ) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…2018b, Kim et al. 2019). These alterations ultimately affect cyanobacterial species composition, frequency, duration, and growth in the aquatic ecosystems worldwide (Hur et al.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…2018b, Kim et al. 2019). These alterations ultimately affect cyanobacterial species composition, frequency, duration, and growth in the aquatic ecosystems worldwide (Hur et al.…”
mentioning
confidence: 98%
“…Backer et al (2015) reported 175 animal deaths and 458 human illnesses in the United States because of harmful algal blooms (HABs) during 2007-2011. Over the decades, climate change, global warming, and eutrophication are likely to alter the biological, chemical, and physical characteristics of aquatic ecosystems (Lee et al 2018b, Kim et al 2019). These alterations ultimately affect cyanobacterial species composition, frequency, duration, and growth in the aquatic ecosystems worldwide (Hur et al 2013, Huisman et al 2018.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[38] utilized spatial autocorrelation to relate the spatial correlation of algae observed along a stream in Namdaecheon. Currently, the K-means algorithm has been widely used to predict and classify water quality in rivers and oceans [39][40][41]. As another method of delineating HAB-prone regions, this study also applied a hot-spot analysis based on the Getis-Ord G* method [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Marine phytoplankton are important food sources for P. viridis that contain a high amount of PUFAs [28]. However, the abundance of plankton is profoundly influenced by the seasonality and environmental factors [29]. P. viridis has the ability to selectively ingest plankton from the water column, depending on the environmental conditions and reproductive cycle [1,30].…”
Section: Introductionmentioning
confidence: 99%